REPORT SURVEY SHIFT FROM TRADITIONAL TO PEER TO PEER (P2P) INFORMATION INTEGRATION - Wicaksana, I Wayan Simri (Universitas Gunadarma, 2007)
Information integration has been developping for fulfill some needs at many areas. Currently, there are still many challenging in information integration issues. Many afford in research and industrial practices have been introduced since two decades. From effort in transfer file, federate, until semantic mediation, and information broker have been done and still continue until today. The challenges for today information integration are well understood. Information integration purpose is in order to manage and use information effectively. Find new approach to overcome previous problem will be still continues. The Peer-to-Peer (P2P) is an interesting approach that was started when internet era become important aspect in human life. The internet bring huge computer network from physical layer to information layer. Especially for information layer, searching appropriate information is a big issue. The P2P based on social life which put in information layer can give other approach compare to database era (traditional information integration). P2P is not new technology, it was introduce at beginning of 80’s, but at this time had difficulties to implement in the real world cause of restricted of technology. This report contains a survey on some approach of information integration. The paper will be divided in some sections. A section will talk the database model for information integration. The next section will describe P2P contribution in information integration.Keywords : survey, information integration, P2P